Food security and socio-economic aspects of agricultural input subsidies. Issue 3 (3rd July 2019) - Solaymani, Saeed; Aghamohammadi, Ebrahim; Falahati, Ali; Sharafi, Saeed; Kari, Fatimah
ABSTRACT: This study is the first attempt at promoting agricultural input subsidy policies in a computable general equilibrium framework on two main dimensions of food security (i.e. food availability and access to food), poverty and income distribution in Malaysia for all ethnic groups. This study investigates the short-run impacts of two subsidy removal policy and one subsidy expansion policy using 2010 input–output table. Results show that both subsidy removal policies negatively influence agricultural sectors and economic growth of Malaysia while the expansion policy influence them positively. The removal policies also decrease food availability and access to food and, consequently, increase poverty at the national level and the poverty level of Malay household, while the expansion policy increases food availability and access to food and alleviate the poverty level of Malay household. The complete removal policy without paddy/rice subsidies increases rice production and raises food availability and access to food commodities (or food security) in the country resulting in a lesser increase in poverty compared to the complete removal policy.